2009
DOI: 10.1128/jcm.00307-09
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for Detection of Enteric Viruses To Enable Syndrome Surveillance of Acute Viral Gastroenteritis

Abstract: Acute gastroenteritis is one of the most common diseases worldwide, with viruses, particularly noroviruses, being the leading cause in developed countries. In The Netherlands, systematic surveillance of gastroenteritis outbreaks of suspected viral etiology was established by the National Institute for Public Health and the Environment in 1994. Since 2002, the total number of outbreaks reported has been increasing, and with that comes the need for sensitive assays that can be performed quickly. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…Previous studies also reported improvements in the detection rate of enteric pathogens by molecular assays (1,7,18,25,36,37,40). The reason why S. enterica was the only pathogen not detected more frequently by MSA than by culture (3.0%) may be the use of a sensitive selective enrichment broth.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies also reported improvements in the detection rate of enteric pathogens by molecular assays (1,7,18,25,36,37,40). The reason why S. enterica was the only pathogen not detected more frequently by MSA than by culture (3.0%) may be the use of a sensitive selective enrichment broth.…”
Section: Discussionmentioning
confidence: 96%
“…However, broad application remains limited due to their assumed high costs, inhibition caused by fecal constituents (22), and the need for specialized laboratories. Due to the high throughput of stool screening and the number of possible enteric pathogens, implementation of a molecular approach which uses multiplexing of targets is mandatory (9,10,20,25,26,36,43,44,47). For the detection of enteric pathogens it has been proven feasible to use molec-ular methods with improved performance and turnaround time (TAT) (7,25,32 MATERIALS AND METHODS mPCR technical validation.…”
mentioning
confidence: 99%
“…Outbreak surveillance has been operational in the Netherlands since 1994 and provides a systematic overview of all notified outbreaks (29). From 1 November 2007 to 1 January 2009, 478 GE outbreaks (3,233 samples) were reported to the surveillance program, and samples were tested for the presence of noroviruses, rotaviruses, enteric adenoviruses, astroviruses, and SaVs by a combination of multiplex RT-PCR assays (3,(28)(29)(30). Outbreaks were attributed to one of the pathogens mentioned above, depending on the diagnostic yield as a proportion of samples tested (3).…”
Section: Methodsmentioning
confidence: 99%
“…Detection of sapoviruses was preformed as described by Svraka et al (30). A multiplex RT-PCR that uses random primers and is sapovirus specific was used; it proved to be more sensitive than previously used sapovirus PCR assays, as described by Svraka et al (30). Sequencing of partial capsid genes of SaVs was performed using primers previously described by Yan et al (35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation